1949
DOI: 10.1103/physrev.75.785
|View full text |Cite
|
Sign up to set email alerts
|

Thresholds for Fast Neutron Fission in Thorium and Uranium

Abstract: 785As to previous range measurements, it appears that our triton range, 60.0±0.6 mm, is in agreement with that found by Livingston and Hoffman, 10 viz. 59.0d=0.6 mm, and also with that found by Rumbaugh, Roberts, and Hafstad, 11 viz., 61 mm (which is, however, not claimed to be very accurate). The latter authors have determined the alpha-range, too, but their The threshold energy for fast neutron fission of thorium and uranium has been measured by using the neutrons from thin lithium films through the Li 7 (p,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1951
1951
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The fission cross section rose rap idly with neutron energy up to about 1.0 Mev and stayed essentially con stant at 1,45 barns from 1.0 to 3.0 Mev. Shoupp & Hill (2) found that U2 a 8 and ThZ3Z fissioned with neutrons above 1.0 Mev, and Grosse, Booth & Dunning (3) fixed the threshold for neutron fission of Pa231 as being higher than thermal energy and less than 2.0 Mev.…”
Section: Fissionability Of Nuclidesmentioning
confidence: 97%
“…The fission cross section rose rap idly with neutron energy up to about 1.0 Mev and stayed essentially con stant at 1,45 barns from 1.0 to 3.0 Mev. Shoupp & Hill (2) found that U2 a 8 and ThZ3Z fissioned with neutrons above 1.0 Mev, and Grosse, Booth & Dunning (3) fixed the threshold for neutron fission of Pa231 as being higher than thermal energy and less than 2.0 Mev.…”
Section: Fissionability Of Nuclidesmentioning
confidence: 97%